Conceptualizing of Green Products on Sustainability Green Repurchase Intention Beauty Products in The Premium Market - Harisnanda, Adriatik; Djumarno, Djumarno (ARE Publisher, 2025)
Objectives: This research aims to analyze the influence of Environmental Concern, Green Trust, Green Price on Sustainability Green Repurchase Intention moderated by Social on L'occitane Products in JABODETABEK - Indonesia. Methodology: The data collection technique is in the form of a questionnaire using an ordinal scale. This research was conducted on 200 L'occitane product users using a quantitative descriptive approach and hypothesis testing. The sampling technique uses random sampling techniques, with data analysis using the Structural Equation Method (Partial least square). Finding: An interesting finding from this research is that Green Price has no effect on Sustainability Green Repurchase Intention among consumers of L'occitane Products in Indonesia, meaning that the level of high or low product prices does not influence high or low sustainability green repurchase intention. Consumers don't mind this, in their minds, green products are imprinted in the minds of L'occitane product users in JABODETABEK - Indonesia. Conclusion: The research results show that Environment Concern has a significant positive effect on Sustainability Green Repurchase Intention, Green Positioning has a significant positive effect on Sustainability Green Repurchase Intention, Green Trust has a significant positive effect on Sustainability Green Repurchase Intention, Social Influence is able to moderate all influences of Green Trust on Sustainability Green Repurchase Intention